2020
DOI: 10.38212/2224-6614.1092
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized gold nanoparticles for sensing of pesticides: A review

Abstract: Pesticides are a family of non-biodegradable chemical compounds which widely used in agriculture to control pests and increase yield production. However, overuse or abuse of pesticides and their metabolites may cause potential toxicity for the environment as well as human health and all other living organisms, even at deficient concentrations. Consequently, the development of sensors for monitoring these compounds is significant. Recently, nanoparticles-based sensors have been extensively employed as a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 165 publications
0
9
0
Order By: Relevance
“…Therefore, simple, rapid, low-cost approaches are still needed to facilitate routine pesticide analysis more conveniently. Colorimetric approaches are simple, cost-effective, and highly selective for determining pesticides compared to other approaches [ 11 , 12 , 13 , 14 ]. The obvious color changes in the sensing probes enable direct observation with the naked eyes upon the addition of target analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, simple, rapid, low-cost approaches are still needed to facilitate routine pesticide analysis more conveniently. Colorimetric approaches are simple, cost-effective, and highly selective for determining pesticides compared to other approaches [ 11 , 12 , 13 , 14 ]. The obvious color changes in the sensing probes enable direct observation with the naked eyes upon the addition of target analytes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, toxins and pesticides can be detected using limited ligands such as DNA aptamers, enzyme cholinesterase, and antibodies. In addition, various detection methods other than colorimetric changes, such as fluorescence, surface-enhanced Raman scattering (SERS), and electrochemical strategies, are used. , Therefore, more examples of specific ligand designs and mechanisms are required to further develop colorimetric sensors for the detection of toxins and pesticides using AuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…DNA oligonucleotides have various applications in antisense delivery, biosensing, catalysis, and nanomaterial assembly . Spherical nucleic acids (SNAs) are interesting structures made of a high density of DNA or RNA oligonucleotides attached to a nanoparticle core, such as a gold nanoparticle (AuNP). The very high extinction coefficient of AuNPs allows visual observation of AuNPs at a low particle concentration. We previously showed that SNAs can strongly adsorb onto various materials’ surfaces, including a few microplastics, due to polyvalent DNA binding interactions. …”
Section: Introductionmentioning
confidence: 99%